CREATIVITY AS A UNIQUE CHARACTERISTIC IN STUDENTS WITH HIGH ABILITIES/GIFTEDNESS:: A LITERATURE REVIEW (Interdisciplinary Studies Journal, 2026)
This article brings together, in a compendium, works published in the Scientific Electronic Library Online (SCIELO) database. It aims to identify literature produced from 2008 to 2022 that addresses the relationship between High Abilities/Giftedness and Creativity, as well as to analyze this characteristic as a useful variable in school-age learners. Through bibliographic research, concepts and characteristics were identified, as well as the various theories surrounding this target audience, considering some determinants and non-determinists, such as family, school, social environment, and economic factors. The methodological approach was designed through qualitative research based on descriptors that determined the selection of 10 articles presented in tables and graphs. The discussions and results found in the articles converge to the conclusion that gifted students generally have greater creativity than their non-gifted peers.
Keywords: Students; High Abilities/Giftedness; Creativity